Pathophysiological examination of arterial hypotension in patients undergoing long-term hemodialysis Second report: baroreflex arch - Kato, Sadaharu; Sugino, Nobuhiro; Igarashi, Naomi; Kubo, Kazuo; Kushiyama, Norio; Suzuki, Yasue; Suzuki, Toshiaki; Kato, Mariko; Nakanishi, Nagako; Kanamaru, Tomoko (Journal of Japanese Society for Dialysis Therapy, 1986)
The interbeat interval response of Valsalva maneuver was significantly lower in hypotensive than normotensive or hypertensive hemodialysis patients (hypotensive (1.22±0.12): vs normotensive (1.40±0.11; p<0.01; or hypertensive (1.35±0.06; p<0.001). Overshoot in arterial pressure after Valsalva maneuver was observed in 1 of 10 hypotensive, 5 of 7 normotensive and all 8 hypertensive patients. These results suggest that baroreflex dysfunction is more significant in hypotensive than normotensive or hypertensive patients. In order to evaluate the abnormal site of the baroreflex arch, cold pressor test, clonidine test and motor nerve conduction velocity were examined in these hemodialysis patients. The changes in mean arterial pressure by cold pressor test (ΔMAP: mmHg) were 10.86±4.41mmHg in the hypotensive, 12.60±7.27mmHg in the normotensive and 21.20±15.25mmHg in the hypertensive patients. These data were not significant compared with 14.92±5.71mmHg in control subjects. Clonidine induced depressor responses in the hypotensive patients; thus it would be working as an α2 adrenoreceptor agonist. Motor nerve conduction velocity was delayed in the hypotensive in comparison with the normotensive and hypertensive patients. These results suggest that hypotensive patients undergoing long-term hemodialysis have baroreflex dysfunction because of abnormal response by Valsalva maneuver but no abnormalities in cold pressor test or clonidine test, indicating intact efferent and central sympathetic activity. However, motor nerve conduction velocity was slightly delayed in the hypotensive patients. The mechanism of hypotension in long-term hemodialysis appears to be multifactorial, and further studies, including surveys of the afferent pathway and vascular reactivity, will be necessary.